Immunotherapy in gastrointestinal cancer: The current scenario and future perspectives. (August 2020) - Abdul-Latif, Mohammed; Townsend, Katherine; Dearman, Charles; Shiu, Kai-Keen; Khan, Khurum
Highlights: Immunotherapy in the form of checkpoint inhibition, adoptive cell therapy and cancer vaccine has been investigated in gastrointestinal cancer. Benefit has been demonstrated in checkpoint inhibition, particularly in oesophageal cancer, gastric cancer and MSI-H colorectal cancer. Pancreatic and liver cancers show little response to immune modulation. Growing interest in combination therapy exploiting VEGF, EGFR and PI3K pathway in context of immune modulation. Abstract: Gastrointestinal cancers include colorectal, gastric, oesophageal, pancreatic and liver cancers. They continue to be a significant cause of mortality and morbidity worldwide. Current treatment strategies include chemotherapy, surgery, radiotherapy and targeted therapies. Immunotherapy has recently been incorporated in treatment regimens for some gastrointestinal malignancies and research into different immune modifying treatments is being carried out in this context. Approaches to immune modulation such as vaccination, adoptive cell therapy and checkpoint inhibition have shown varying clinical benefit, with most of the benefit seen in checkpoint inhibition. This review summarises recent advances and future direction of immunotherapy in patients with gastrointestinal malignancies.